2008 IEEE International Symposium on Information Theory 2008
DOI: 10.1109/isit.2008.4594986
|View full text |Cite
|
Sign up to set email alerts
|

Capacity bounds for the Gaussian Interference Channel

Abstract: The capacity region of the two-user Gaussian Interference Channel (IC) is studied. Three classes of channels are considered: weak, one-sided, and mixed Gaussian ICs. For the weak Gaussian IC, a new outer bound on the capacity region is obtained that outperforms previously known outer bounds. The channel sum capacity for some certain range of the channel parameters is derived. It is shown that when Gaussian codebooks are used, the full Han-Kobayashi achievable rate region can be obtained by using the naive Han-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
408
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(423 citation statements)
references
References 28 publications
12
408
3
Order By: Relevance
“…Treating interference as noise with Gaussian codebooks has been shown to be sum-capacity optimal in the so called very-weak interference regime [71][72][73]. 2.…”
Section: Max-i Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…Treating interference as noise with Gaussian codebooks has been shown to be sum-capacity optimal in the so called very-weak interference regime [71][72][73]. 2.…”
Section: Max-i Problemmentioning
confidence: 99%
“…Unfortunately, the capacity expression in (49) is considered "uncomputable" in the sense that we do not know how to explicitly characterize the input distributions that attain its convex closure. Moreover, it is not clear whether there exists an equivalent single-letter form for (49) Because of "uncomputability" the capacity expression in (49) has received little attention, except for the following: in [79] the limiting expression was used to show that limiting to jointly Gaussian distributions in suboptimal; in [72] the limiting expression was used to derive the sum-capacity in the very weak interference regime; and in [90] it was shown that in the high-power regime the limiting expression normalized by the point-to-point capacity (i.e., the degrees of freedom (DoF)) can be single letterized.…”
Section: Interference Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum achievable rate R dn 2 (w 1 , w 2 ) is the minimum of the right-hand sides of (5) and (6). For link 2, we note that the maximum achievable rate does not necessarily exploit the signal-to-interference-plus-noise (SINR) ratio at RX 2 to the full extent.…”
Section: An Achievable Rate Regionmentioning
confidence: 99%